New Approaches With Natural Product Drugs for Overcoming Multidrug Resistance in Cancer - Dinic, Jelena; Podolski-Renic, Ana; Stankovic, Tijana; Bankovic, Jasna; Pesic, Milica (Current Pharmaceutical Design, 2015)
Resistance to chemotherapeautic drugs is one of the main obstacles to effective cancer treatment. Multidrug resistance (MDR) is defined as resistance to structurally and/or functionally unrelated drugs, and has been extensively investigated for the last three decades. There are two types of MDR: intrinsic and acquired. Tumor microenvironment selection pressure leads to the development of intrinsic MDR, while acquired resistance is a consequence of the administered chemotherapy. A central issue in chemotherapy failure is the existence of heterogeneous populations of cancer cells within one patient and patient-to-patient variability within each type of cancer. Numerous genes and pathways contribute to the development of MDR in cancer. Point mutations, gene amplification or other genetic or epigenetic changes all affect biological functions and may lead to the occurrence of MDR phenotype. Similar to the characteristics of cancerogenesis, the main features of MDR include abnormal tumor vasculature, regions of hypoxia, aerobic glycolysis, and a lower susceptibility to apoptosis. In order to achieve a lethal effect on cancer cells, drugs need to reach their intracellular target molecules. The overexpression of the efflux transporter P-glycoprotein (P-gp) in MDR cancer cells leads to decreased uptake of the drug and intracellular drug accumulation, minimising drug-target interactions. New agents being or inspired by natural products that sucessfully target these mechanisms are the main subject of this review. Two key approaches in combating MDR in cancer are discussed (i) finding agents that preserve citotoxicity toward MDR cancer cells; (ii) developing compounds that restore the cytotoxic activity of classic anticancer drugs.
Keywords: plant secondary metabolites